2011
DOI: 10.1007/s12187-011-9116-4
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Influences of Proactive and Reactive Subtypes of Aggression

Abstract: The contextual factors associated with proactive and reactive subtypes of aggression have not been well-studied. In order to address this omission in the literature, the current study evaluated relations between perceived best friend delinquency, negative life events, and proactive and reactive aggression in a sample of 147 school-age children (M age =8.22 years; 54.4% male). Multiple regression analyses suggested that negative life events were uniquely associated with reactive aggression and best friend delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The strongest positive correlation was observed between conduct symptoms and proactive aggression. This is in line with previous empirical studies showing that proactive aggression is more strongly associated with delinquency and conduct disorder than reactive aggression (Fite et al, 2012;Raine et al, 2006;Vitaro et al, 1998). Scarpa, Haden and Tanaka (2010) found that reactive aggression was significantly related to increased internalizing behaviors and attention deficits, while proactive aggression was significantly related to increased hyperactivity/impulsivity and delinquent behavior problems.…”
Section: Discussionsupporting
confidence: 92%
“…The strongest positive correlation was observed between conduct symptoms and proactive aggression. This is in line with previous empirical studies showing that proactive aggression is more strongly associated with delinquency and conduct disorder than reactive aggression (Fite et al, 2012;Raine et al, 2006;Vitaro et al, 1998). Scarpa, Haden and Tanaka (2010) found that reactive aggression was significantly related to increased internalizing behaviors and attention deficits, while proactive aggression was significantly related to increased hyperactivity/impulsivity and delinquent behavior problems.…”
Section: Discussionsupporting
confidence: 92%
“…As explained above, this finding may also refer to the links between problematic peer relationships and proactive aggression. Consistent with previous studies (Fite et al, 2010;Fite et al, 2012), mild deviance was also found to be a significant predictor of proactive aggression. Peer delinquency is believed to effect proactively aggressive behavior through peer socialization.…”
Section: Discussionsupporting
confidence: 91%
“…Prior findings regarding the relations of peer deliquency with reactive and proactive aggression is somewhat controversial. While a recent study (Fite et al, 2012) found that best friend deliquency was positively associated with proactive aggression and unrelated to reactive aggression, Fite et al (2010) reported that peer delinquency was positively associated with both proactive and reactive aggression. In the present study we focused on "peer deliquency" rather than "best friend deliquency."…”
Section: Discussionmentioning
confidence: 90%
“…Shields and Cicchetti (1998) examined the interplay of aggression, emotion, and attention among youth with and without maltreatment histories and found that physically abused youth exhibited higher levels of reactive aggression than youth without such histories. Additional research has found a unique association between stressful life events and reactive, but not proactive, aggression (Brown, Fite, & Poquiz, In press; Fite, Wimsatt, et al, 2012; Silvern & Griese, 2012). In contrast, Connor and colleagues (2004) examined correlates of reactive and proactive aggression among psychiatrically referred youth.…”
Section: Child Maltreatment and Reactive And Proactive Aggressionmentioning
confidence: 99%
“…First, most of this research has focused on broadly defined aggression, ignoring subtypes (i.e., reactive and proactive aggression) of aggressive behavior (Bandura, 1973; Friend, 2014). Second, studies that have examined the link between child maltreatment and reactive (in response to a perceived threat) and proactive (goal-oriented) aggression have produced mixed results (Fite, Wimsatt, Elkins, & Grassetti, 2012; Shields & Cicchetti, 1998). Another limitation of the current literature is that few studies have examined the mechanisms through which maltreatment experiences might contribute to reactive and proactive aggression.…”
mentioning
confidence: 99%